2007
DOI: 10.1291/hypres.30.161
|View full text |Cite
|
Sign up to set email alerts
|

Benidipine Attenuates Glomerular Hypertension and Reduces Albuminuria in Patients with Metabolic Syndrome

Abstract: Recent studies have shown that metabolic syndrome is associated with an increased risk for chronic kidney disease. We recently found that the prevalence of sodium-sensitive hypertension in patients with metabolic syndrome was significantly higher than that in patients with essential hypertension but without metabolic syndrome. We therefore assessed the effects of benidipine, a long-acting calcium channel blocker, on the sodium sensitivity of blood pressure and renal hemodymamics in 5 patients with metabolic sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…In addition, recent studies in humans have shown that metabolic syndrome is associated with an increased risk for a reduced GFR and microalbuminuria (9,20). Interestingly, it has been reported that patients with essential hypertension and metabolic syndrome have glomerular hypertension and increased albumin excretion (52).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, recent studies in humans have shown that metabolic syndrome is associated with an increased risk for a reduced GFR and microalbuminuria (9,20). Interestingly, it has been reported that patients with essential hypertension and metabolic syndrome have glomerular hypertension and increased albumin excretion (52).…”
Section: Discussionmentioning
confidence: 99%
“…Some CCBs,however,selectivelydilaterenalafferentarteriolesr athert hane fferentarterioles,a nd therebyincreasei ntra-glomerularpressure, possiblyleading tothe developmentorfurtherprogression of nephropathy [16].Benidipine hasbeen shownto improvethe vascularr esistanceo frenale fferentarteriolesand toreducei ntra-glomerularpressurei nanimal models [16], hypertensivep atients withn ephropathy [17]a nd thosewithm etabolicsyndrome [18].Amlodipine and nifedipine,in contrast,do notdilaterenale fferentarterioless om arkedlyast heydilateafferentarterioles,a ccording too ne report [16].Furthermore, benidipine hasinhibitory effects on aldosterone production viab lockade of T-type voltage-dependentCa 2+ channels [19]a nd on the urinary protein excretion occurring in responseton itricoxide (NO)p roduction whichi smediated byBH 4 (tetrahydrobiopterin) [20]. Theserenalp rotectivee ffects of benidipine mayaccountfort he differencei nrenale ventr atesobserved among the CCBsin the presentclinicalstudy.Benidipine morem arkedlydecreasesBP and urinary protein thanamlodipine,a ss howni naprevious study [11 -13].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, benidipine causes dilation of renal efferent arterioles and inhibition of aldosterone production, which cannot be explained by the block of L-type Ca 2+ channels. (Kawata et al, 1997;Morikawa et al, 2002;Uzu et al, 2007;Akizuki et al, 2008). These pharmacological effects appear to be due to the additional block of T-type Ca 2+ channels.…”
Section: Introductionmentioning
confidence: 99%